Typhonium flagelliforme decreases telomerase expression in HeLa cervical cancer cells - Purwaningsih, Endang; Suciati, Yulia; Widayanti, Etty (Universa Medicina, 2016)
Background Cancer cells have a relatively high telomerase activity compared to normal cells, so that cancer cells have the ability for continued proliferation and uncontrolled mitosis. Telomerase is an enzyme responsible for the length of telomeres, DNA segments located at the ends of eukaryotic chromosomes. Natural materials such as rodent tuber (Typhonium flagelliforme) have anticancer potential. The purpose of the present study was to determine the effects of Typhonium flagelliforme extract on telomerase expression in HeLa cervical cancer and T47D breast cancer cells. Methods This experimental laboratory study was conducted on cultured HeLa and T47D cancer cell lines, with normal Vero cells as controls, and using RPMI and M199 culture media. The study comprised three groups, i.e. controls, and groups receiving Typhonium flagelliforme extract at doses of ½ IC50 and IC50. Telomerase expression was measured by immunohistochemistry (IHC). Analysis of variance and LSD multiple comparison test were used to analyze the data. Results Telomerase expression in cancer cells showed significantly higher values compared to normal Vero cells. Typhonium flagelliforme extract was capable of significantly decreasing telomerase expression in cancer cells receiving the extract. Conclusion Typhonium flagelliforme extract at different doses is capable of decreasing telomerase expression more effectively in cervical cancer cells than in breast cancer cells. This study shows that Typhonium flagelliforme may have anti-cancer activity, necessitating further investigations.